2006
DOI: 10.2337/db06-0377
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chromosome 2 Obesity Loci on Cardiovascular Complications of Insulin Resistance in LDL Receptor–Deficient C57BL/6 Mice

Abstract: Previous characterization of mouse chromosome 2 identified genomic intervals that influence obesity, insulin resistance, and dyslipidemia. For this, resistant CAST/Ei (CAST) alleles were introgressed onto a susceptible C57BL/6J background to generate congenic strains with CAST alleles encompassing 67-162 Mb (multigenic obesity 6 [MOB6]) and 84 -180 Mb (MOB5) from mouse chromosome 2. To examine the effects of each congenic locus on atherosclerosis and glucose disposal, we bred each strain onto a sensitizing LDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Variation in genes identified in mice has been shown to affect the corresponding phenotypes in humans (24,52,75). These studies have also identified potential relations between MetS traits, showing that the same or nearby genes affect multiple MetS components (37,140).…”
Section: Use Of Mouse Models In Dissecting Metsmentioning
confidence: 88%
“…Variation in genes identified in mice has been shown to affect the corresponding phenotypes in humans (24,52,75). These studies have also identified potential relations between MetS traits, showing that the same or nearby genes affect multiple MetS components (37,140).…”
Section: Use Of Mouse Models In Dissecting Metsmentioning
confidence: 88%
“…In contrast, although the MOB6 congenic showed comparable glucose levels to the LDLR Ϫ/Ϫ strain, atherosclerosis was 2-fold reduced in this strain. 104 Plasma lipids and lipoprotein profiles were nearly identical between MOB6 and MOB5 strains. This study illustrates that individual traits associated with the metabolic syndrome can be separated and that insulin resistance was more important for promoting atherosclerotic lesions than elevated plasma glucose levels.…”
Section: Genome Scanningmentioning
confidence: 88%
“…103 The separation of glucose and atherosclerosis was also seen in a study of 2 congenic strains of C57BL/6 carrying loci derived from CAST/Ei (CAST). 104 Two regions of chromosome 2 alleles from CAST mice were introgressed into the C57BL/6 background and subsequently bred to LDLR Ϫ/Ϫ mice to create hyperlipidemic backgrounds for the CAST alleles. Mice fed chow and Western diets were studied for measures of glucose and lipid homeostasis and atherosclerosis.…”
Section: Genome Scanningmentioning
confidence: 99%
“…Studies in hypertensive rats (SHHR) and mice (eNos 3null ) have contributed a wealth of knowledge regarding how hypertension may impact morbidity and mortality either in isolation or in the context of the metabolic syndrome [5,6]. Similarly, diet-induced and spontaneous models of dyslipidemia in mice, such as the Ldlr null and ApoE null strains are providing clues to how alterations in circulating lipids may exacerbate cardiovascular disease [7,8]. Finally, models where hyperglycemia results from a genetic mutation (Ins2 Akita ), or following autoimmune attack of pancreatic beta cells (NOD Mouse, BB Rat), are providing systems to test the role of hyperglycemia in the array of pathophysiologies associated with metabolic syndrome [9,10].…”
mentioning
confidence: 98%